Comparison of Outcomes of Kidney Transplantation in Diabetic and Non-Diabetic Patients: Kidney Transplantation in Diabetic and Non-Diabetic Patients - Naeem, Manzoor Ahmad; Naseer, Alia; Naseem, Sidra; Bilal, Mohammad Asad; Naeem, Usra; Raza, Ali; Rehman, Iqra (Pakistan BioMedical Journal, 2025)
When opposed to long-lasting dialysis, kidney transplantation offers patients with end-stage renal illness a higher chance of mortality and a better standard of life. It is still up for debate whether kidney transplantation is more beneficial for diabetic individuals in contrast to those lacking the disease. Objective: To compare outcomes of kidney transplantation in diabetic and non-diabetic patients. Methods: Data from 100 patients was collected from Sheikh Zayed Hospital Lahore, Pakistan. The following variables were assessed to compare the consequences of transplants in patients with and without diabetes: per graft fluid collection, superficial infection of the wounded area, cut-off hernia, shallow injury dehiscence, cellulitis, seroma, fascial breaking down, deep wound contamination, hypertension, and mortality and recuperation. Fisher’s exact test was applied to test statistically significant variances in outcomes and p-value≤0.05 was considered significant. Results: A statistically significant variance was observed in per graft fluid collection among diabetic and non-diabetic kidney transplant patients i.e., 68% vs 32% respectively with p-value≤0.05. A significant difference was observed in the occurrence of incisional hernias between the two groups, with a high rate in non-diabetic patients. Facial dehiscence also showed a statistically significant difference, with a higher incidence in non-diabetic patients (p=0.010). Conclusions: It was concluded that diabetes significantly impacts certain post-transplant outcomes, such as fluid collection. In contrast, other outcomes like incisional hernia and facial dehiscence are more prevalent in non-diabetic patients who had kidney transplants.